Research priorities for privately protected areas - Fitzsimons, James A.; Mitchell, Brent A. (Frontiers in Conservation Science, 2024)
The important role of private land conservation, and particularly privately protected areas (PPAs), in contributing towards global conservation is increasingly recognised. With an increase in the extent of PPAs, under a variety of different legal regimes and governance types, comes an increasing number of ecological, social, governance and legal research questions. Research into various aspects of PPAs has been growing. In compiling the IUCN's Guidelines for Privately Protected Areas, a range of research questions were posed to the IUCN World Commission on Protected Areas Specialist Group on Privately Protected Areas and Nature Stewardship sought to gain the views of researchers and practitioners involved in PPAs regarding what they considered to be priorities for research. Responses were higher on enabling factors and mechanisms specific to PPAs and somewhat fewer on ecological and social outcomes. These results can be used to guide future research efforts that will be most meaningful to improve PPA take up, effectiveness and longevity, noting there is a need for researchers, practitioners, landowners and managers, and policymakers to collectively set the research agenda.